1995
DOI: 10.1271/bbb.59.1949
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of Microorganisms by the Supercritical Carbon Dioxide Micro-Bubble Method

Abstract: Lactobacillus brevis and Saccharomyces cerevisiae were completely sterilized by the supercritical (SC) CO2 micro-bubble method. Gaseous (G) and liquid (LQ) CO2 were used in a similar manner to compare the sterilizing effect. Among the three treatments, the microorganisms were only effectively sterilized by the SC CO2 treatment at 25 MPa and 35 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…In recent years, supercritical CO 2 and/or highpressure CO 2 has been applied to inactivate various enzymes that are responsible for degradation in the quality of food. [7][8][9] We also have reported the inactivation of enzymes 10,11) and microorganisms 12,13) by batch treatment with microbubbles of pressurized CO 2 . In these studies, various enzymes and microorganisms were effectively inactivated in aqueous solution under high-pressure carbonation.…”
mentioning
confidence: 93%
“…In recent years, supercritical CO 2 and/or highpressure CO 2 has been applied to inactivate various enzymes that are responsible for degradation in the quality of food. [7][8][9] We also have reported the inactivation of enzymes 10,11) and microorganisms 12,13) by batch treatment with microbubbles of pressurized CO 2 . In these studies, various enzymes and microorganisms were effectively inactivated in aqueous solution under high-pressure carbonation.…”
mentioning
confidence: 93%
“…[1][2][3][4][5][6] The mechanism by which HCT acts is still poorly understood, but previous reports have suggested that a decrease in cytoplasmic pH is likely to be the major reason for the inactivation of microorganisms by HCT. [7][8][9][10] Heat treatment induces several changes in cells, including alteration in the appearance of the cell, leakage of low-molecular-weight materials, protein coagulation, and DNA and RNA breakdown.…”
mentioning
confidence: 99%
“…There have been many studies on the effects of high pressure carbon dioxide treatment (HPCT) on the inactivation of bacteria under moderate temperature (approximate 20 to 40˚C) and pressure (approximately 5 to 35 MPa) (Nakamura et al, 1994;Ishikawa et al, 1995;Erkmen, 2001;Shimoda et al, 2001Shimoda et al, , 2002. For the sterilization of bacterial spores, it has been thought to be effective to decrease the heat tolerance of bacterial spores, and then to inactivate them by subsequent HT.…”
mentioning
confidence: 99%